The Spread of Shi'a and Its Activities in Nigeria - Mohammed Maga Sule; Muhammad Maigari Abdullahi (Journal of Islamic Studies and Humanities, 2019)
The aftermath of the Iranian revolution and emergence of Shia Immamiya as the religion of government in Iran in 1979. The Razavi charitable Endowment under the Iran’s supreme religious leader has been spending a lot of money, especially in Africa to indoctrinate and convert Muslims to Shia. The paper traced the origin of Shia in Nigeria. Identified the factors that facilitated the spread of Shia in Nigeria. A desk review methodology was adopted. The study found out that the Iranian government has devoted a lot of funds to Africa and under the pretext of aid in the area of building Mosques, establishing schools and giving the scholarship to study in Iran. It has been observed that ignorance of Shia among most Islamic scholars, teachers, and preachers has contributed its spread until when Nigerians started studying in Universities in Saudi Arabia, the real identity of Shia is known.